Model Matematika Konflik Tiga Kompartemen (Model Diskret) - Sugiyanto Sugiyanto; Muhammad Wakhid Musthofa (Jurnal Fourier, 2014)
The conflict between groups of people is a serious problem for the people of Indonesia. Mathematical Model of trying to resolve this problem. In this study the number of police officers involved have been in accordance with the amount of power a group of warring parties, so that the police can relieve the community because the amount of power that is balanced. In the case study of conflicts in South Lampung as much as 700 police officers who have been involved is in compliance. The victim died because police were too late in fielded as many as 700 police.